Symptoms overlooked in hospitalized cancer patients: Impact of concurrent symptoms on overlooked by nurses. Issue 2 (19th March 2013) - Miyajima, Kaya; Fujisawa, Daisuke; Hashiguchi, Saori; Shirahase, Joichiro; Mimura, Masaru; Kashima, Haruo; Takeda, Junzo
Abstract: Objective: Physical and psychological symptoms in cancer patients are frequently overlooked by medical staff. However, little is known regarding the potential impacts of concurrent physical and psychological symptoms on the overlooking of other symptoms. The aim of this study was to examine the impact of concurrent symptoms on the overlooking of other symptoms in cancer inpatients. Method: A total of 255 cancer inpatients in the general wards of one university hospital, who were referred to the palliative care team, were included. On the day of referral, nurses and patients were independently assessed for the presence of the following eight symptoms: pain, fatigue, nausea and vomiting, shortness of breath, lack of appetite, dry mouth, sleep problems, and distressed feelings. The presence of delirium was also separately assessed by nurses and psychiatrists on the team. A total of nine symptoms detected by nurses and those reported by patients or psychiatrists were compared, and logistic regression analysis was performed to identify the variables associated with the overlooking of these symptoms. Results: The most frequently reported symptom was pain (76.5%), followed by distressed feelings (49.8%), sleep problems (34.1%), and delirium (25.1%). The proportion of those overlooked was more than one quarter (25.0–63.6%) for all symptoms except pain (12.8%). Significant associations were found between the overlooking of shortness of breath and concurrent delirium (odds ratio [OR] = 110.9); the overlooking of sleep problems and concurrent lack of appetite (OR = 9.1); and the overlooking of distressed feelings and concurrent dry mouth (OR = 27.7). No patient demographic characteristic was associated with the overlooking of any other symptoms. Significance of results: The presence of some specific concurrent symptoms is likely to lead to the overlooking of other symptoms in cancer inpatients by nurses. Comprehensive assessments of physical and psychological symptoms in daily clinical practice are needed.